2021
DOI: 10.1111/febs.16306
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of type 2 diabetes and the impact of altered metabolic interorgan crosstalk

Abstract: Diabetes is a complex and multifactorial disease that affects millions of people worldwide, reducing the quality of life significantly, and results in grave consequences for our health care system. In type 2 diabetes (T2D), the lack of β‐cell compensatory mechanisms overcoming peripherally developed insulin resistance is a paramount factor leading to disturbed blood glucose levels and lipid metabolism. Impaired β‐cell functions and insulin resistance have been studied extensively resulting in a good understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 321 publications
(481 reference statements)
0
28
0
Order By: Relevance
“…(Table 3). A previous study showed that smoking, older age, diabetes mellitus and hypertension can increase systemic soft tissue remodeling [20][21][22]. Therefore, our findings can be explained by the fact that the systemic predisposition of SP was strengthened by the abovementioned risk factors.…”
Section: Discussionmentioning
confidence: 56%
“…(Table 3). A previous study showed that smoking, older age, diabetes mellitus and hypertension can increase systemic soft tissue remodeling [20][21][22]. Therefore, our findings can be explained by the fact that the systemic predisposition of SP was strengthened by the abovementioned risk factors.…”
Section: Discussionmentioning
confidence: 56%
“…The body's system maintains glucose levels through the pair of opposing hormones, insulin and glucagon (Unger and Orci, 2010). However, type 2 diabetics have low insulin sensitivity, impaired glucose tolerance, and decreased insulin- Frontiers in Pharmacology frontiersin.org stimulated glucose uptake; therefore, glucose level becomes too high (Lebovitz, 2001;Sanches et al, 2021). PPARγ is a key regulator of adipogenic differentiation, and its role has been well established.…”
Section: Discussionmentioning
confidence: 99%
“…A full analysis of T2D pathophysiology is beyond the scope of this review, but, as discussed in a recent review by Galicia-Garcia et al [ 6 ], the mechanisms underlying insulin production and release, and its detection and uptake by target tissues, are all tightly regulated, and defects in any of these may lead to metabolic imbalances and ultimately to the development of T2D [ 3 , 6 ]. For example, impairments in any of the pathways involved in insulin binding can lead to reduced glucose uptake, resulting in higher circulating glucose levels (hyperglycemia) and placing increasing demands on insulin-producing pancreatic beta cells [ 3 , 7 ] and, as noted above, impaired insulin detection and/or uptake by target tissues such as skeletal muscle, adipose tissue, and the liver can result in insulin resistance [ 3 , 7 ]. Of note, this also leads to inflammation in the target tissues, with increases in circulating levels of proinflammatory cytokines [ 3 , 7 ].…”
Section: Pathophysiology Of T2dmentioning
confidence: 99%
“…For example, impairments in any of the pathways involved in insulin binding can lead to reduced glucose uptake, resulting in higher circulating glucose levels (hyperglycemia) and placing increasing demands on insulin-producing pancreatic beta cells [ 3 , 7 ] and, as noted above, impaired insulin detection and/or uptake by target tissues such as skeletal muscle, adipose tissue, and the liver can result in insulin resistance [ 3 , 7 ]. Of note, this also leads to inflammation in the target tissues, with increases in circulating levels of proinflammatory cytokines [ 3 , 7 ].…”
Section: Pathophysiology Of T2dmentioning
confidence: 99%